Record of short-lived “orogen” on Eurasian continental margin by South China Sea obduction preserved in Taiwan collision - Lo, Yun-Chieh; Chen, Chih-Tung; Lo, Ching-Hua; Chung, Sun-Lin; Yeh, Meng-Wan (Frontiers in Earth Science, 2023)
The Taiwan mountain belt is the result of an arc-continent collision following the total subduction of the South China Sea and subsequent closure of the Luzon forearc, a process important in the accretionary growth of continents. Due to the oblique convergence, the southern tip of Taiwan Island is experiencing incipient collision, which is key to observing the oceanic-continental subduction transition. Within the monotonous turbidite extensively exposed on the Hengchun Peninsula as an uplifted Manila Trench accretionary wedge, the Shihmen Conglomerate, as a few intercalated lenses of coarse mafic pebbles, represents a dramatic change in sediment provenance and the causal tectonic event. New zircon U-Pb and amphibole 40Ar/39Ar ages are obtained from sediments, including sands and mafic pebbles that are either gabbro or foliated amphibolite. The 22–24 Ma zircon crystallization ages confirm the South China Sea origin of the mafic clasts, while the much younger 13 ± 2 Ma amphibole 40Ar/39Ar isochron ages from foliated amphibolites suggest a later thermal-tectonic event other than seafloor metamorphism. The amphibole 40Ar/39Ar ages overlap with the biostratigraphic age (∼11–14 Ma), indicating that the mafic source rocks were exhumed and eroded in a high-relief topography immediately after metamorphism. Detrital zircon U-Pb ages from a sandy layer within the conglomerate are also mostly identical to those from the mafic pebbles. Since the paleocurrent of the Shihmen Conglomerate was similar to that of the neighboring turbidites, which were derived from major rivers draining the southeastern Chinese continent, the provenance of the mafic pebbles and sands was best explained as an isolated subaerial mountain on the Eurasian continental margin with a very limited temporal and spatial extent, as the detrital products are poorly distributed. The most likely cause of the ephemeral mountain was the obduction of the South China Sea onto the Eurasian continental margin when the latter first impinged on the Philippine Sea Plate at the Manila Trench, where the gabbroic oceanic crust was uplifted and exhumed, followed by dynamic metamorphism along the basal thrust.